Кiнематична зсувна в’язкiсть рiдких лужних металiв - Makhlaichuk, V. N. (Publishing house "Academperiodika", 2018)
The origin of kinematic shear viscosity in liquid alkaline metals has been studied. It is shown that, since the depth of the well in the potential of pair interaction between ions is small in comparison with the energy of thermal motion of those ions, the mechanism of kinematic shear viscosity formation is not an activation one. The main mechanism consists in the momentum transfer from one layer to another and depends on the layer “roughness”. In accordance with the generalized similarity principle, liquid alkaline metals are shown to belong to the same similarity class, and a similar character of changes in the isobars of the kinematic shear viscosity of liquid alkaline metals is observed only if this principle is applicable. A formula for the kinematic shear viscosity is proposed. The agreement of the results obtained with experimental data is quite satisfactory.